A multi-pronged scoping review approach to understanding the evolving implementation of the Smallpox and Polio eradication programs: what can other Global Health initiatives learn? - Meike Schleiff; Adetoun Olateju; Ellie Decker; Abigail H. Neel; Rasheedat Oke; Michael A. Peters; Aditi Rao; Olakunle Alonge (BMC Public Health, 2020)
Abstract Background Previous initiatives have aimed to document the history and legacy of the Smallpox Eradication Program (SEP) and the Global Polio Eradication Initiative (GPEI). In this multi-pronged scoping review, we explored the evolution and learning from SEP and GPEI implementation over time at global and country levels to inform other global health programs. Methods Three related reviews of literature were conducted; we searched for documents on 1) the SEP and 2) GPEI via online database searches and also conducted global and national-level grey literature searches for documents related to the GPEI in seven purposively selected countries under the Synthesis and Translation of Research and Innovations from Polio Eradication (STRIPE) project. We included documents relevant to GPEI implementation. We conducted full text data analysis and captured data on Expert Recommendations for Implementing Change (ERIC) implementation strategies and principles, tools, outcomes, target audiences, and relevance to global health knowledge areas. Results 200 articles were included in the SEP scoping review, 1885 articles in the GPEI scoping review, and 963 documents in the grey literature review. M&E and engagement strategies were consistently translated from the SEP to GPEI; these evolved into newer approaches under the GPEI. Management strategies including setting up robust record systems also carried forward from SEP to GPEI; however, lessons around the need for operational flexibility in applying these strategies at national and sub-national levels did not. Similarly, strategies and lessons around conducting health systems readiness assessments prior to implementation were not carried forward from SEP to GPEI. Differences in the planning and communication strategies between the two programs included fidelity to implementation blueprints appeared to be higher under SEP, and independent monitoring boards and communication and media strategies were more prominent under GPEI. Conclusions Linear learning did not always occur between SEP and GPEI; several lessons were lost and had to be re-learned. Implementation and adaptation of strategies in global health programs should be well codified, including information on the contextual, time and stakeholders’ issues that elicit adaptations. Such description can improve the systematic translation of knowledge, and gains in efficiency and effectiveness of future global health programs.